Task-Based Language Teaching - Gomez, Leonardo (CIEX JOURNAL, 2020)
In this session, three core approaches/models (Ellis or Long, Willis, and Nunan) to task-based language teaching (TBLT) will be outlined. A critical look at what constitutes a task will be discussed, as well as a presentation of sample tasks for each. Emphasis will be placed on when and how teachers can exploit critical incidents to address linguistic deficiencies and generate better output.